The message of Obadiah, Nahum and Zephaniah : the kindness and severity of God - Bridger, Gordon, 1932- (Downers Grove, IL : Inter-Varsity Press, 2010)
These Old Testament books teach us some major truths: the importance of focusing on God, who is personal, sovereign, righteous and loving; of facing up to sin and judgment; of responding in repentance and faith; and of the hope of future salvation and restoration--From publisher description.
The message of Obadiah. The sovereignty of God : who is really in charge? (1, 15, 21) ; The judgments of God : who will answer for what? (2-15) ; The triumph of God : what hope is there? (15-21) -- The message of Nahum. Divine judgment : theologically explained (1:2-15) ; Divine judgment : historically illustrated (2:1-3:19) -- The message of Zephaniah. God's message of judgment (1:2-2:3) ; Judgment and hope for the nations (2:4-3:8) ; Hope and restoration for God's people (3:9-20)
Includes bibliographical references.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc